Plasma-Enhanced Atmospheric-Pressure Spatial ALD of Al2O3 and ZrO2. (16th August 2016) - Creyghton, Yves; Illiberi, A.; Mione, A.; van Boekel, W.; Debernardi, N.; Seitz, M; van den Bruele, Fieke; Poodt, P.; Roozeboom, Fred
Abstract : Non-thermal plasma sources are known to lower the operation temperatures and widen the process windows in thermal ALD of thin-film materials. In spatial ALD, novel plasma sources with exceptional dimensional and chemical stability are required to provide the flow geometries optimized for efficient transport and use of radicals (O, N, H, OH, NH, etc. ).This paper describes our preliminary efforts to provide and examine the required linear scalable plasma sources in spatial ALD reactors. The effectiveness of close-proximity direct and remote plasma sources was demonstrated for thin dielectric films of Al2 O3 and ZrO2 deposited at temperatures ranging from 20 to 100°C. Both direct and remote SDBD-type (Surface Dielectric Barrier Discharge) plasma sources were applied using conventional metal precursors and O2 /N2 plasma. The remote plasma designs proved advantageous in avoiding electrical source-substrate interactions which often result in layer or substrate damage caused by filamentary plasma discharges impacting the substrate.